Pest categorisation of Anthonomus bisignifer. (11th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; Navarro, Maria Navajas; Niere, Björn; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of the strawberry blossom weevil, Anthonomus bisignifer Schenkling, (Coleoptera: Curculionidae), for the EU. Anthonomus bisignifer is a well‐defined and distinguishable species, recognised as an occasional pest of strawberry ( Fragaria ) fruit production in Japan where it is also feeds on Rubus and Rosa spp. Adults clip developing buds, preventing fruit development and reducing yield. Losses are variable and are likely to depend on the cultivars attacked. Severe damage to Fragaria spp. has been reported but is rare. Flowers of ornamental garden Rosa spp. are more commonly damaged. Anthonomus bisignifer is not known to occur in the EU. A. bisignifer is listed in Annex IIAI of Council Directive 2000/29/EC. Host plants for planting could provide a pathway although only a few non‐EU countries can export Fragaria plants for planting to the EU and A. bisignifer is not known to occur in any of them. However, Rubus and Rosa plants for planting could provide a potential pathway to introduce A. bisignifer . Considering climatic similarities of the region where A. bisignifer occurs and where hosts occur in the EU, A. bisignifer has the potential to establish within the EU. There would be one generation per year, as in Japan. Impacts could be expected on field grown and protected Fragaria, field grown Rubus and garden Rosa spp. There is uncertainty regarding which other hosts exist within Rosaceae, hence impacts could potentially be seen on other species too. Phytosanitary measures are available to reduce the likelihood of introduction of A. bisignifer . All criteria assessed by EFSA for consideration as a potential Union quarantine pest are met. As A. bisignifer is not known to occur in the EU, this criterion assessed by EFSA to consider it as a Union regulated non‐quarantine pest is not met.